Facing the Future. - Zhang Yage (Beijing Review, 2024)
The article discusses the increasing use of digital avatars by business leaders and media institutions in China. Liu Qiangdong, the founder and CEO of JD.com, recently appeared as a digital avatar in livestreaming sessions to promote products and connect with consumers. This trend is part of a larger shift towards digital livestreaming in China's e-commerce industry, with avatars offering advantages such as availability and cost-effectiveness. Digital avatars are also being used in the communications and media field, with state broadcaster CCTV and China.org.cn employing avatars to provide updates and host video content. However, there are technical challenges and ethical considerations associated with the use of avatars.